Free Will and Relationality: Theological, Philosophical and Scientific Perspectives - Visala, Aku (Philosophy, theology and the sciences, 2021)
Systematic theology of the 20th century saw a significant turn to relational accounts of human personhood. As a consequence, the context of the free will discussion changed significantly. If humans were to have any kind of free will, it could no longer be considered as some kind of innate capacity of an atomistic individual. Rather, free will (the capacity to act in a morally responsible way) should be grounded in our relational nature as social and cultural beings. Let us call this the relational roots of the free will thesis. In what follows, I want to explore this thesis, its problems, and prospects. I will do this with tools from analytic philosophy as well as evolutionary human science. I will begin by making some remarks about the concept of free will itself. After that, I will examine a theological and relational account of free will by the theologian Robert Jenson. After outlining the core problem with Jenson's account, I will go on to highlight some philosophical and scientific accounts that might be of help in developing a relational account of free will.